Youth Problem Behaviors Eight Years after Implementing the Communities That Care Prevention System in a Community-Randomized Trial - Hawkins, J. David (2014)
IMPORTANCE: Community-based efforts to prevent adolescent problem behaviors are essential to promote public health and achieve collective impact community-wide. OBJECTIVE: To test whether the Communities That Care (CTC) prevention system reduced levels of risk and adolescent problem behaviors community-wide 8 years after implementation of CTC. DESIGN: A community-randomized trial. SETTING: Twenty-four small towns in 7 states, matched within state, assigned randomly to control or intervention group in 2003. PARTICIPANTS: All fifth-grade students attending public schools in study communities in 2003-04 who received consent from their parents to participate (76.4% of eligible population). A panel of 4407 fifth graders was surveyed through 12th grade with 92.5% of the sample participating at the last follow-up. INTERVENTION: A coalition of community stakeholders received training and technical assistance to install CTC, used epidemiologic data to identify elevated risk factors and depressed protective factors for adolescent problem behaviors in the community, and implemented tested and effective programs for youths aged 10 to 14, their families, and schools to address their community's elevated risks. MAIN OUTCOME MEASURES: Levels of targeted risk; sustained abstinence and cumulative incidence by grade 12 and current prevalence of tobacco, alcohol, and other drug use, delinquency, and violence in 12(th) grade. RESULTS: By spring of 12(th) grade, students in CTC communities were more likely than students in control communities to have abstained from: any drug use (RR=1.32; 95% CI 1.06 to 1.63); drinking alcohol (RR=1.31; 95% CI 1.09 to 1.58); smoking cigarettes (RR=1.13; 95% CI 1.01 to 1.27), and engaging in delinquency(RR=1.18; 95% CI 1.03 to 1.26). They were also less likely to ever have committed a violent act (RR=0.86; 95% CI 0.76 to 0.98). There were no significant differences by intervention group in targeted risks, the prevalence of past-month or past-year substance use, or past-year delinquency or violence. CONCLUSIONS AND RELEVANCE: Using the CTC system continued to prevent the initiation of adolescent problem behaviors through 12th grade, 8 years after implementation of CTC and 3 years after study-provided resources ended, but did not produce reductions in current levels of risk or current prevalence of problem behavior in 12(th) grade.